Correlation Between Mesio-Distal Teeth Diameters and Arch Width - Francesca Cremonini; Carla Provenzano; Mario Palone; Giorgio Alfredo Spedicato; Paolo Albertini (Association of Support to Oral Health Research (APESB), 2021)
Objective: To verify the existence of a correlation between the mesio-distal size of teeth and the arch width by analyzing the data separately for maxillary and mandibular arch in patients with ideal occlusion. Material and Methods: 58 patients with ideal occlusion were studied, for a total of 276 files analyzed. Dental casts were then scanned using a professional scanner (Epson Perfection v 330) and images were obtained in TIFF format at 600 dpi. All single teeth measurements were carried out for all teeth of both arches using the VAM software (Vectra, Canfield Scientific, Fairfield, NJ, USA). The repeatability and reproducibility of the measurement method were evaluated using the Gauge R&R method. In case a correlation between tooth size and arch size is found to be significant, a linear regression analysis can be applied through the following statistical relationship: y=a+b*x, where y is the result (inter-molar distance "AvgB66" or inter-canine distance "Cusp 33"), and x the specific tooth. The a and b respectively represent the intercept (point of intersection between the line and the y axis) and the slope of the line that describes the regression ratio. Results: The statistical analysis highlights a significant correlation (p<1%) between the results of the mesio-distal measurements of each tooth and the two variables considered to define the size of each arch ("AvgB66" and "Cusp 33"). Based on these results, a numerical relationship "y=a+b*x" has been extrapolated. Thus, it is possible to calculate the estimated inter-molar or inter canine distance necessary to have the teeth aligned. Conclusion: The inter-canine and inter-molar distances can be estimated starting from measuring the mesio-distal diameter of a single tooth.